KEMAMPUAN MENGANALISIS UNSUR-UNSUR TEKS CERITA FABEL SISWA KELAS VIII SMP NEGERI 07 PANGKALAN KURAS KABUPATEN PELALAWAN - Asrianti, Depi; Hakim, Nursal; Elmustian, Elmustian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Fables are told not only for entertaining purposes, but also as a medium of moral education in which noble values are tucked into, namely the introduction of manners. To analyze a text, there are two aspects, namely the aspect of intrinsic elements and intrinsic elements. The analysis of intrinsic elements of literary works is an analysis of the internal elements that build a literary work. Therefore, in analyzing researchers more leads to the analysis of intrinsic elements. This study aims to describe the level of ability to determine the intrinsic elements of fable texts at Pangkalan Kuras Pelalawan 7th High School Students.In this study, the instruments used to collect data are questions in the form of questionnaires that will be distributed to respondents. Data collection techniques by giving tests to students by asking students to answer test questions given by researchers about test questions consisted of 20 multiple choice questions. Data analysis uses the percentage of right and wrong answers. The results of the analysis show that the ability to determine text themes were low with an average of 68.98. The ability to determine fable text characters were medium with an average of 84.40. The ability to set the background of the fable story text were medium category with an average of 84.62. The ability to determine the flow of fable story text werehigh with an average of 85.79. The ability to determine the point of view of fable story text were high with an average of 86.75. The ability to determine the characterization of fable story texts were medium with an average of 82.41. The ability to determine the mandate of story text fables were medium with an average of 80.72.Key Words: Analyzing Ability, Text Elements, Fable